Analysis of the Problems Behind Students' Low Understanding of Learning Javanese Local Content in the Digital Era in Fifth-Grade Elementary School - Khilwiyatul Lu'lu'a; Sri Sami Asih (STAI Hubbulwathan Duri, 2025)
The Javanese language, particularly its unggah-ungguh or speech levels, plays a vital role in conveying cultural values. However, fifth-grade students at SDN Kalisegoro, Semarang, show low proficiency in using Krama, the formal Javanese register. The rise of digital technology has contributed to decreased exposure and practice of traditional linguistic structures in everyday communication. This qualitative descriptive study employed a case study approach to investigate students' understanding of unggah-ungguh, the factors affecting its usage, and possible interventions. Data were collected through semi-structured interviews with two teachers and four students, as well as document analysis. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Findings reveal that while students recognize basic Krama vocabulary, they struggle to construct sentences correctly and confidently. Contributing factors include minimal use of Krama at home, lack of motivation, limited school-based reinforcement, and the influence of informal digital communication. Teachers primarily rely on traditional lecture methods, which further reduce student engagement. The results suggest a need for innovative, student-centered learning strategies that integrate digital tools while reinforcing cultural values. To strengthen unggah-ungguh usage, schools should adopt interactive methods such as gamification and digital storytelling. Parental involvement and school policies that support cultural language use are also essential. These efforts can help preserve Javanese speech etiquette among younger generations in the digital era.